Urban And Regional Agglomeration In The Brazilian Amazon: Comparing Metropolitan Development In Belém And Manaus - Santos, Tiago Veloso (Advances in Social Sciences Research Journal, 2023)
This article demonstrates, by drawing a comparison between the two main metropolitan agglomerates, Belem and Manaus, the different ways of production in the regional space of the Brazilian Amazon. Based on the organization, systematization, and analysis of data regarding the main elements of the urban structure in both agglomerates, namely, the patterns of housing settlements of upper, middle, and lower classes, the distribution of industrial zones, and the patterns of urban expansion, we sought to highlight the intra-urban differences between the two metropolises, considering their importance in the regional urban network.